PALEOGEOGRAPHIC FEATURES OF SKELEVATSKA SUITE METACONGLOMERATES OF KRIVOY ROG STRUCTURE - Matischuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Paleogeographic reconstruction of skelevatka suite is carrried out on the base on the following methods: comparison of the intensity coefficients of of weathering and sedimentary differentiation by A. Predovsky, N. Strahov’s method – "Ideal profile", the ratio between elementsindicators and facial conditions of sedementation – depositional environments. By using SAK method of V. Golovenok and making the comparison between chemical compositions of rocks of skelevatska suite and average clark abundance of rock-forming oxides in magmatic rocks the reconstruction of climatic conditions of sedimentation in the suite is made. The use of stratigraphic analysis allowed to identify the possible sources of clastic material and ways of its transportation. The results of relation between the coefficients of intensity of weathering – W and sedimentary differentiation – d obtained for rocks of skelevatska suite are compared with similar ones obtained from the different types of zones of tectonic regime. They indicate the fact that stable tectonic regime on the border of two subsuite has changed by moderately activated one. The growing role of tectonic activity during the accumulation of sediments of the second subsuite is also proved by a low degree of maturity of the clay sediment and the increasemen of alumino-module. The method by Srtachov shows that the content of most petrochemical units in the suite rises from psammites to pelites, maintaining the overall regularity typical of the "ideal profile", from the coastal to "pelagic" area. The distribution of petrochemical units in the "ideal profile" can be characterized as smooth, which is typical for alluvial-proluvialsedimentation in the coastal environment. This fact is also proved by the presence of the two peaks of maximum values of elements found in the conglomerates and shales. Similar results are obtained when using ratios of elements-indicators. Reconstruction of climatic conditions indicates the formation of rocks of skelevatska suite in the conditions of hot and moisture climate, and also on the formation of sediments in the transition from continental to marginal-marine conditions. On the basis of formational analysis identified the sources of clastic material. These sources were rocks occurred to the East from the basin of sedimentation, namely the rocks of Middle Dnieper complex. They include the rock asocciation of greenstone structures rfepresented by metamorphosed volcanic rocks of basic, intermediate and acid composition, terrigenous rocks and granitoids of the sursko-tokovskoe intrusive complex.